DETERMINANT FACTORS OF PRODUCT ATTRIBUTES TO CONSUMER BUYING BEHAVIOR OF MOTORCYCLES - Ngantung, Valensia Naomi (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Large number of people using motorcycles, makes companies and producers need to analyze and search more on the consumer buying behavior towards purchasing motorcycle. This will help the companies to make good decisions on what kinds of motorcycles that need to be produced. The company will have a step ahead in knowledge than others about the consumer needs and wants of a motorcycle because motorcycle industry is one of the fastest growing industry. The objective of this research is to know the factors of product attributes that influence consumer buying behavior of motorcycles in Manado. The population in this research are all the motorcycle owners in Manado with sample as many as 100 respondents.Â  Factor Analysis Method were used to analyze the twenty variables in this research. The result and conclusions are from twenty variables observed, eighteen variables formed six factors that drive consumers to buy a motorcycle. Those factors are product, quality, trust, value, design, and usage. There are two variables that do not significantly influence consumers to buy motorcycles, namely : easy-to-use, and discount price. Keywords: consumer buying behavior, product attributes.